The Effect of Natural Disaster Risk and Socio-Demographic on Poverty in East Java: A Review of Panel Data 2015-2022 - Nadia Putri Kurnia; Wiwin Primandhana; Wirya Wardaya (Cita konsultindo, 2024)
Poverty is a human condition that has difficulty meeting the needs of life and is an unsolved problem in Indonesia. East Java Province has the highest poverty compared to other provinces and has a moderate to high risk of natural disasters. The purpose of this study is to determine the influence of natural disaster risk factors on poverty in addition to socio-demographic factors of districts and cities in East Java Province in 2015-2022. This research method uses panel data regression analysis with data sources from the Central Statistics Agency and the National Disaster Management Agency. The results of the analysis with the Random Effect Model show that the risk of natural disasters is positively significant to poverty. Meanwhile, socio-demographic factors consisting of open unemployment rate and population number have a significant positive effect on poverty. However, the human development index and gross regional domestic product have a significant negative effect on poverty.